2016
DOI: 10.1002/hed.24532
|View full text |Cite|
|
Sign up to set email alerts
|

Long‐term outcomes after multidisciplinary management of T3 laryngeal squamous cell carcinomas: Improved functional outcomes and survival with modern therapeutic approaches

Abstract: BACKGROUND Evaluate long-term outcomes after initial definitive or adjuvant radiotherapy for T3-larynx cancers. METHODS We reviewed 412 patients treated for T3 laryngeal squamous cell cancer 1985–2011. RESULTS 10-year OS was 35%; disease-specific-survival (DSS), 61%; locoregional control (LRC), 76%; freedom from distant metastasis, 83%. Chemotherapy, age, performance status <2, node-negative status, and glottic sub-site were associated with improved survival (all P<0.03). Larynx preservation with induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…Multiple studies have demonstrated that pretreatment comorbidity status is an independent predictor of overall survival (OS). (19, 1113) …”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that pretreatment comorbidity status is an independent predictor of overall survival (OS). (19, 1113) …”
Section: Introductionmentioning
confidence: 99%
“…Table summarizes a literature review of the different therapeutic options. In several studies of surgical treatments, including total laryngectomy, the 5‐year OS rates ranged from 41% to 85.5% . Although it is difficult to compare these earlier results directly with our findings, the survival rates in our study tended to be favorable.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of LP, Timme et al calculated a 2-year LEDFS rate of 40% in patients with T3 disease treated with IV-CRT 24. Fuller et al reported 5-year LFS rates of 38% and 62% in patients with T3 disease treated with definitive RT or systemic CRT, respectively, and 5-year LEDFS rates of 37% and 59% in patients with T3 disease treated with definitive RT or systemic CRT, respectively 25. Therefore, our findings appear to demonstrate more favorable outcomes of disease control, survival, and LP, compared to previous studies.…”
mentioning
confidence: 99%
“…Laryngeal squamous cell carcinoma (SCC) is managed by both surgical and nonsurgical treatment modalities and its management has evolved over recent years, trending towards nonsurgical, organ‐preservation treatment in the primary setting. The current management for advanced laryngeal SCC is supported by evidence from the landmark Veterans Affairs Larynx Trial and subsequent organ‐preservation studies in laryngeal SCC which recommend delivering nonsurgical, organ‐preserving regimens to patients with good pretreatment function . After primary nonsurgical treatment, up to 25% of laryngeal cancers recur, therefore requiring salvage total laryngectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The current management for advanced laryngeal SCC is supported by evidence from the landmark Veterans Affairs Larynx Trial 1 and subsequent organ-preservation studies in laryngeal SCC which recommend delivering nonsurgical, organ-preserving regimens to patients with good pretreatment function. 2,3 After primary nonsurgical treatment, up to 25% of laryngeal cancers recur, therefore requiring salvage total laryngectomy. The optimum management of the neck in a locally recurrent laryngeal SCC after initial radiotherapy (RT) or chemoradiotherapy (CRT) remains unclear, with no high-level evidence on the topic and the majority of data arising from retrospective case series.…”
Section: Introductionmentioning
confidence: 99%